INDEPENDENT LEARNING, EDUCATIONAL. ORGANIZATIONAL PART OF THE PEDAGOGICAL PROCESS - Kazimov Jamshid Shamshidinovich (American Journals, 2022)
In this article, it is reported that education - independent education, education - self-education, education - independent education, information - independent education, taking into account the characteristics of the processes of development and educational relations as the basis of the development of the student's personality, they can be distinguished as constituent parts of the whole pedagogical process.
Keywords: : education